Temporal trends in readmissions after transcatheter aortic valve replacement. (25th November 2020) - Arora, S; Strassle, P.D; Hendrickson, M.J; Sitammagari, K; Qamar, A; McRee, C.W; Yeung, M; Vavalle, J.P
Abstract: Background: Although readmissions after transcatheter aortic valve replacement (TAVR) were frequent in initial experiences, it is unknown if the incidence of readmission has changed with technological advances and other factors. Purpose: Assess temporal trends in 30-day readmission after TAVR Methods: Hospitalizations of adults aged ≥50, with aortic stenosis and undergoing elective TAVR or SAVR between 2012 and 2016 in the National Readmission Database were analyzed. Causes of 30-day readmission were classified as cardiovascular (CV) and non-cardiovascular (non-CV). Poisson regression was used to assess quarterly trends in TAVR and SAVR readmissions. Results: Overall, 29, 031 TAVR and 72, 412 SAVR hospitalizations were included (weighted N 56, 858 TAVR and 151, 899 SAVR), and 14% were readmitted within 30-days (TAVR: 15%; SAVR: 13%). Of all the readmissions, 38% were cardiovascular (TAVR: 35%; SAVR: 40%). Between January 2012 and November 2016, the incidence of overall 30-day readmission significantly declined from 20% to 13% (CIE −0.13, 95% CI: −0.13, −0.13, p<0.0001) after TAVR and from 15% to 12% (CIE −0.05, 95% CI: −0.05, −0.05, p<0.0001) after SAVR. When stratified by readmission cause, the incidence of both CV (7.2% to 4.2%; CIE −0.18, 95% CI: −0.18, −0.18, p<0.0001) and non-CV readmissions declined after TAVR (14% to 9.0%; CIE −0.24, 95% CI: −0.24, −0.24, p<0.0001), Figure 1. CV readmissions (5.6% to 4.7%; CIE −0.05, 95% CI: −0.05, −0.05, p<0.0001) and non-CV readmissions (9.7% to 7.7%; CIE −0.12, 95% CI: −0.12, −0.12, p<0.0001) also declined after SAVR. Finally, the cost of TAVR admissions decreased for both patients who were not readmitted within 30-days (CIE −2.3, 95% CI: −2.5, −2.0, p<0.0001) and patients who were readmitted (CIE −1.9, 95% CI: −2.6, −1.2, p<0.0001) from 2012 to 2016. Costs of readmission have not changed (CIE −0.23, 95% CI: −0.80, 0.35, p=0.44). Conclusion: Readmissions after TAVR have declined over the last several years, likely due to improvements in technology and operator experience, greater attention to comorbidities, and reductions in inpatient complications. More work is needed to reduce further inpatient complications and the incidence of readmission. Funding Acknowledgement: Type of funding source: None